Annexin A1 Tripeptide Mimetic Increases Sirtuin-3 and Augments Mitochondrial Function to Limit Ischemic Kidney Injury - Suliman, Hagir; Ma, Qing; Zhang, Zhiquan; Ren, Jiafa; Morris, Benjamin T.; Crowley, Steven D.; Ulloa, Luis; Privratsky, Jamie R. (Frontiers in Physiology, 2021)
Background: Acute kidney injury (AKI) is one of the most common organ failures following surgery. We have developed a tripeptide mimetic (ANXA1sp) of the parent annexin A1 molecule that shows promise as an organ protectant limiting cellular stress; however, its potential as a kidney protective agent remains unexplored, and its mechanism of action is poorly understood. Our hypothesis was that ANXA1sp would limit kidney injury following surgical ischemic kidney injury. Methods: In blinded fashion, wildtype mice were assigned to receive vehicle control or ANXA1sp 1 hour prior to and 1 hour after kidney vascular clamping. Our primary outcomes were markers of kidney injury and function as measured by serum creatinine and histologic injury scoring of kidney tissue sections. Immunofluorescence microscopy, real-time PCR and western blot were used to assess cell death, oxidative stress, and mitochondrial biomarkers. An in vitro model of oxygen-glucose deprivation in immortalized kidney tubule cells was used. Results: ANXA1sp given prior to and after ischemic kidney injury abrogated ischemic kidney injury. ANXA1sp limited cell death both in vivo and in vitro and abrogated oxidative stress following ischemia. ANXA1sp significantly increased expression of markers associated with protective mitophagy and limited expression of markers associated with detrimental mitochondrial fission. ANXA1sp upregulated expression of the mitochondrial protectant sirtuin-3 (SIRT3) in the mitochondria of kidney tubular cells. Silencing of SIRT3 reversed ANXA1sp-mediated protection against hypoxic cell death. Conclusions: ANXA1sp limits kidney injury, upregulates SIRT3, and preserves mitochondrial integrity following ischemic kidney injury. ANXA1sp holds considerable promise as a perioperative kidney protectant prior to ischemia inducing surgery and kidney transplantation.